Paris Saponin VII Induces Apoptosis and Cell Cycle Arrest in Erythroleukemia Cells by a Mitochondrial Membrane Signaling Pathway - Lin, Xin; Gajendran, Babu; Varier, Krishnapriya M.; Liu, Wuling; Song, Jingrui; Rao, Qing; Wang, Chunlin; Qiu, Jianfei; Ni, Wei; Qin, XuJie; Wen, Min; Liu, Haiyang; et al. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background and Purpose: Leukemia is considered a top-listed ailment, according to WHO, which contributes to the death of a major population of the world every year. Paris Saponin VII (PS), a saponin which was isolated from the roots of Trillium kamtschaticum, from our group, was reported to provide hemostatic, cytotoxic and antimicrobial activities. However, its molecular mechanism underlying the anti-proliferative effects remains unclear. Thus, this study hypothesized to assess that mechanism in PS treated HEL cells. Methods: The MTT assay was used to analyze the PS inhibited cell viability in the HEL cells. We further found that PS could induce S phase cell cycle arrest through flow cytometry as well as the western blot analysis of intrinsic and extrinsic apoptotic molecules. Results: The MTT assay showed the IC50 concentration of PS as 0.667μM. The study revealed that PS treatment inhibits cell proliferation dose-dependently. It further caused mitochondrial membrane potential changes by PS treatment. Mechanistic protein expression revealed a dose-dependent upsurge for Bid and Bim molecules, while Bcl2 and PARP expression levels were significantly (P<0.05) down-regulated in PS treated HEL cells resulting in caspase -3 release and increased the Bim levels upon 24h of incubation. Conclusion: These findings indicate that PS possesses an excellent anti-leukemic activity via the regulation of the mitochondrial pathway, leading to S phase cell cycle arrest and caspase-dependent apoptosis, suggesting it as a potential alternative chemotherapeutic agent for leukemia patients.
Keywords: cell cycle